1977
DOI: 10.2337/diab.26.6.591
|View full text |Cite
|
Sign up to set email alerts
|

HLA System in Japanese Patients with Diabetes Mellitus

Abstract: Seventy-eight Japanese diabetics were HLA-typed, with special reference to age at onset, insulin dependency, and family history. HLA-A9, B5, and BW40 were increased, but A1, A3, and B8, which are found frequently among Caucasians, were almost absent among Japanese healthy controls as well as diabetics. J-1, a Japanese specific subclass of BW22, was significantly increased in juvenile-onset diabetics as compared with controls or diabetics with late onset. J-1 was also increased in the diabetics with insulin dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…HLA typing in this study revealed that the frequencies of HLA-BW54 and HLA-DR4, which are strongly associated with Japanese IDDM (12,26,27), are lower in these negative convertors of ICA than in persistently ICA-positive subjects (Table 3). On the other hand, the frequencies of HLA-BW54 and HLA-DR4 were high in persistently ICA-positive patients with NIDDM and IGT with slowly progressive clinical courses.…”
Section: Discussionmentioning
confidence: 66%
“…HLA typing in this study revealed that the frequencies of HLA-BW54 and HLA-DR4, which are strongly associated with Japanese IDDM (12,26,27), are lower in these negative convertors of ICA than in persistently ICA-positive subjects (Table 3). On the other hand, the frequencies of HLA-BW54 and HLA-DR4 were high in persistently ICA-positive patients with NIDDM and IGT with slowly progressive clinical courses.…”
Section: Discussionmentioning
confidence: 66%
“…The black patients with Type 1 diabetes did not show any increase in the frequencies of CW3, B15, and B18 as has been found in European Caucasoids, nor of BW54 and B12 as observed in Japanese [1][2][3]. Studies in American blacks or Nigerians have not shown any significant association at the B locus [15][16][17].…”
Section: Discussionmentioning
confidence: 78%
“…HLA antigens associated with Type I diabetes in White Caucasoids include CW3, CW4, B8, B15, DW3, DW4, DR3 and DR4 [1]. In the Japanese, the disease has been associated with HLA-DYT and BW54 [2,3] while in South African Indians an association with B8 has been shown [4]. Other studies have shown a relationship with DR3 and DR4 in American blacks [5] and with either B8 or B14, which are cross-reacting antigens, in South African blacks [6].…”
mentioning
confidence: 99%
“…Our data also agree with some reports from Western countries [2,3], despite the fact that there are certain differences between Type 1 diabetes in Japanese and Caucasoid people. Typical juvenileonset Type 1 diabetes is less frequent in Japan than in Western countries [8] and is associated with different HLA antigens from those seen in Caucasoid patients [9,10]. Islet-cell antibodies are uncommonly demonstrated in Japanese patients with Type 1 diabetes [11].…”
Section: Discussionmentioning
confidence: 99%